Parent’s Needs During Their Child Hospitalization - Miķelsone, Madara; Sīpols, Jānis (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The child's hospitalization is always associated with distress to child and his parents, because of unfamiliar environment. Although the child is in the center of the care, parents are encouraged to stay with their child at hospital. To achieve successful co-operation between parents and health care practitioners it is necessary to identify child`s and also their parent`s needs. Parental satisfaction with provided care depends on the quality of cooperation, which is an important indicator of the quality of the care. Aim of the study was to determine parental needs and level of their satisfaction during child hospitalization in one of the inpatient health care institutions in Latvia. Research results showed most important and less important parental needs and their level of satisfaction as well as implications were developed for further research